ARGUMEN GREEN SUFISME SEBAGAI ETIKA LINGKUNGAN (Analisis Filosofis) - Bambang Irawan; Mohd Syahiran Abdul Latif; Ismail Fahmi Arrauf Nasution (Religia, 2022)
The research is concerned with the Sufis’ thoughts in responding to the ecological crisis faced by a human.Their responses are depicted in their texts—that text is used as the source of primary and secondary texts.The primary texts were the works of Ibn Arabi, such as Fusus al-Hikam and Futuhat al-Makiyyah, alsothe work of Hossein Nasr entitled Islamic Cosmological Doctrines. The secondary texts were the thoughts ofscientists who proposed the same themes. Then, this research used a qualitative analysis and hermeneuticapproach. This research also analyzed the reality of the existing natural environment. Relevant referencessupported it. The researcher constructed deep philosophical thoughts to find essential meanings and valuesabout the natural environment that humans need to develop. Several philosophical thoughts form the basis of green Sufism: microcosmos and macro-cosmos theory, emanation theory, and Illumination Theory